Biomonitoring of persistent pollutants in grey seal (Halichoerus seagrypus) pups from the Gulf of Riga, Baltic Sea - Salcedo, S.; Di Marzio, A.; Martínez-López, E. (Marine pollution bulletin, 2024)
We analyzed for the first time the concentration of potentially toxic trace elements Hg, As, Pb, Cr and Se and POPs (PCBs and OCPs) in tissues of 41 grey seal pups (Halichoerus grypus) stranded on the shores of the Gulf of Riga. Lanugo was the sample with the highest concentrations of all trace elements except Hg. The concentrations found in this biological matrix appeared as follows: Hg (2.50 ± 1.43 μg/g); Se (1.22 ± 0.82 μg/g); Cr (0.96 ± 1.51 μg/g); As (0.95 ± 1.03 μg/g); Pb (0.50 ± 0.60 μg/g). POPs were∑PCB (0.566 ± 0.520 μg/g), ∑DDT (0.522 ± 0.454 μg/g), ∑HCH (0.043 ± 0.045 μg/g) and Chlordane (0.041 μg/g). We detected brain Hg levels above the threshold described for neurobehavioural changes and some individuals also exceeded the toxic threshold described for PCBs. Thus, the health of grey seal pups could be affected by both groups of pollutants. [Display omitted] •Metals and POPs were measured in tissues of grey seals from Gulf of Riga.•Lanugo of grey seal pups was in general the matrix with the highest levels for all trace elements and Hg the metal with the highest levels.•POPs levels in the following order ∑PCB > ∑DDT > ∑HCH > Chlordane•The Se:Hg molar ratio was <1 in brain and muscle, with brain Hg concentrations above the threshold described for neurobehavioural changes.•Some individuals exceeded the toxic threshold described for PCBs.